Wildlife Management in Himachal Pradesh - Chauhan, B. S. (Indian Forester, 1991)
Himachal Pradesh with its diverse climatic conditions has a large variety of Flora and Fauna. Till the recent past Wildlife Management received very little attention. With the new thinking an importance of wildlife concentrated efforts are being made in this direction of scientific management of wildlife in the State. These include Protection of Wildlife and its habitat, creation and extension of Protected Areas, studies on typical Western Himalayan Fauna, Captive breeding and Rehabilitation of Endangered Species, TraIning of Staff and a well organised publicity campaign.